PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS LEARNING CYCLE (5E) UNTUK MEMFASILITASI PEMAHAMAN KONSEP SISWA SMP - Dhita Murti Santari; Wahyu Budi Saputra; Palupi Sri Wijayanti (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2018)
The purpose of this research is (1) to produce products LKS based Learning Cycle (5E), (2) to know whether the resulting LKS meets the valid criteria and (3) by using this LKS, understanding concept of student can be improved. This research is a Research and Development (RnD). The produre used is defining, planning, and development. The technique of data collection in this research is form of validation experts to 3 validators, test questions, and questionnaire. The technique of questionnaire data analysis used in expert validation and students respond to LKS developed, beside that test question are used in the assessment of students learning outcomes. The result of this research and development is: (1) Based on the form validation of three validators is the expert of media by 80% (very valid category), the expert of materials by 80% (very valid category), and the teacher by 90% (very valid category). (2) The percentage of students learning outcomes reached 50%, the percentage of students questionnaire responses reached 71.56% (positive category). (3) The result of the analysis of the indicators of concept understanding ability are obtained, the first indicator reached 100%, the second indicator reached 58.33%, the third indicator reached 33.33%, the fourth indicator reached 41.67%, the fifth indicator reached 100%, the sixth indicator reached 50%, and the seventh indicator reached 100%.